Identification and characterization of the products of six region III flagellar genes (flaAII.3 through flaQII) of Salmonella typhimurium. - Homma, M (1988)
A portion of flagellar region III of the Salmonella typhimurium genome has been cloned and shown to contain six genes: flaAII.3, flaAIII, flaS, flaR, flaQI, and flaQII. Of these, all but flaQI were known to exist from mutant studies; the former flaQ has been renamed flaQII. The genes were shown by minicell analysis to encode proteins with apparent molecular masses of 28, 48, 15, 46, 17, and 37 kilodaltons, respectively. The presence of a flagellar-gene-specific promoter in the vicinity of flaQI was established by testing expression of the plasmid-encoded tetracycline resistance gene in artificial constructions. In minicell preparations, the flaAII.3 and flaR products were found principally in the cytoplasmic fraction; the rest were found principally in the membrane fraction. A comparison between the homologous genes of S. typhimurium and Escherichia coli confirmed that their genomic organizations were similar and that their products had similar molecular masses and isoelectric points.